Green sythesis of silver nanoparticles using vangueria infausta and parinaricuratellifolia leaf extract and evaluation on their antifungal activities - Mariwowo, Evelyn (Midlands State University, 2017)
A green approach was used in the synthesis of silver nanoparticles which is an easy, cheap, eco-friendly and a fast method in achieving stable silver nanoparticles over a long period of time. Plant leaves extract from Parinari Curatellifolia and Vangueria Infausta were used in the synthesis after optimizing different parameters (temperature, silver nitrate concentration and amount of extract. The optimum conditions achieved for the synthesis of silver nanoparticles (AgNPs) using Parinari Curatefollia were at a emperature of 70 oC, 5 mM silver nitrate and 9 ml of the extract. For Vangueria Infausta the temperature was at 50 oC, 5 mM silver nitrate and 10 ml of the plant extract. The characterization of the synthesized AgNPs was done using Ultraviolet-Visible (UV-Vis) spectrophotometer and Fourier Transform Infrared (FTIR) spectroscopy. From the UV-Vis analysis the Surface Plasmon resonance (SPR) band of AgNPs using Parinari Curatellifolia leaf extract was found out to be at 430 nm and for Vangueria Infausta leaf extract it was at 415 nm. The groups which were responsible for the capping of silver nanoparticles as evidenced by the FTIR were the O-H, C-O and C=O bonds which were present at 3642.06 cm-1 and 1657.76 cm-1 respectively for the AgNPs obtained from Parinari Curatellifolia leaf extract and at 3638.45 cm-1 and 1655.73 cm-1 respectively for AgNPs obtained from Vangueria Infausta leaf extract. The synthesised silver nanoparticles from both plants were found out to be stable for over two months as evidenced by the UV-Vis Spectroscopy. The Agar disk diffusion method was used for antifungal studies and the synthesized AgNPs were effective against Trichoderma, Penicillium, Fusarium and Saccharomyces Cerevisiae fungi as indicated by the clear inhibition zones. Thus Parinari Curatellifolia and Vangueria Infausta extracts can be applied in the synthesis of AgNPs for application as fungicides as indicated by the clear inhibition zones.